1991
DOI: 10.1063/1.859831
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional kinetic field-reversed equilibria

Abstract: A two-dimensional kinetic description of field-reversed equilibria has been developed. Three equilibrium models are presented: a kinetic model, a rigidly rotating model, and a magnetohydrodynamics (MHD) model. The kinetic model of equilibrium provides spatial distributions of the macroscopic moments, including velocity shear, that are in good agreement with experimental observations. The rigidly rotating and MHD models allow more general pressure profiles than previous studies. These models, which allow the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…where B θ = 0 is assumed, and ψ = Ψ p /2π = r 0 B z rdr is the normalized radial magnetic flux, J θ is the toroidal current density of plasma, P ′ is the derivative of pressure with respect to ψ and µ 0 is the vacuum permeability. Studies have shown that in present experiments kinetic effects of the equilibrium is small [7], and the FRC experimental study confirmed the applicability of the G-S equation [1,8], at least for the inner region of FRCs.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…where B θ = 0 is assumed, and ψ = Ψ p /2π = r 0 B z rdr is the normalized radial magnetic flux, J θ is the toroidal current density of plasma, P ′ is the derivative of pressure with respect to ψ and µ 0 is the vacuum permeability. Studies have shown that in present experiments kinetic effects of the equilibrium is small [7], and the FRC experimental study confirmed the applicability of the G-S equation [1,8], at least for the inner region of FRCs.…”
Section: Introductionsupporting
confidence: 84%
“…In Eqs. (7) and (8) b s is the normalized magnetic field b ≡ B(r)/B e at the separatrix, σ and α are free parameters. In the 2PE and 3PE models [Eqs.…”
Section: The Mrr Equilibrium Modelmentioning
confidence: 99%
“…where B θ = 0 is assumed, and ψ = Ψ p /2π = r 0 B z r dr is the normalized poloidal magnetic flux, J θ is the toroidal current density of the plasma, P is the derivative of pressure with respect to ψ and μ 0 is the permeability of vacuum. Studies have shown that at equilibrium, kinetic effects are negligible in a standard FRC [10], and an FRC experimental study confirmed the applicability of the G-S equation [1,11], at least for the inner region of FRCs.…”
Section: Introductionmentioning
confidence: 67%
“…In terms of the normalized parameters defined above, equation ( 16) can be written in different forms for each model described by equations ( 4)- (10):…”
Section: A Step-by-step Methods For a Quasi-1d Equilibrium Solutionmentioning
confidence: 99%
See 1 more Smart Citation